Pengaruh Inhibitor Ekstrak Propolis Terhadap Laju Korosi Pada Aplikasi Baja Zincallume - Piran, Nicolaush N.; Budiarsa, I Nyoman; Santhiarsa, I..Gusti..Ngurah Nitya (Teknik Desain Mekanika; Vol 10 No 3 (2022): Juli 2022 : Teknik Desain Mekanika, 2022)
Abstractt The choice of materials for building frames from lightweight and corrosion-resistant steel is one of the decisions that must be made by a researcher. The selection and process is determined before giving a coating or mixture to the material, so that its strength, durability and use can satisfy consumers. One of the efforts to increase the corrosion resistance of steel is by adding inhibitors, where in this study the addition of Green Inhibitors with Kele-Kele Propolis extract was used(Trigona Honey). In this study, there were two treatments, namely without and with Green Inhibitor Kele-Kele Propolis extract on zincallume (G550) steel test material I.? profile and I.U profile in the real environment (hot and rainy environmental conditions) for 2 weeks (336 hours). Based-on-the-test-results,-it-is-known-that-the green inhibitor treatment with Kele-Kele Propolis extract can reduce the-corrosion-rate-of Zincallume-steel, both in-the I.? profile and the-I.U profile. Keywords: Zincalume Steel, Inhibitor, corrosion rate, efficiency.